Fatigue life prediction of magneto-rheological elastomers in magnetic field. (24th February 2021) - Hosseini, Seyyed Mohammad; Shojaeefard, Mohammad Hassan; Saeidi Googarchin, Hamed
Abstract: Fatigue life is one of the most important characteristics of materials. Predicting fatigue life in magnetorheological elastomer (MRE) under combined and repetitive loads is an unavoidable step to increase the safety coefficient of MREs. In this study, high-temperature vulcanization silicon rubber (HTVSR) based MREs were fabricated by incorporating the different soft carbonyl iron particles (CIP) that samples with 10%, 20%, and 30% of CIP volume were made. Fatigue behavior of MRE under the combination of compression-tension and torsion loading in the presence and absence of magnetic fields was studied by using the multiaxial fatigue testing machine. The relationship between maximum energy density function ( W max ) and fatigue life ( N ) was achieved that it can predict fatigue life in MREs. The results showed that the dissipation energy was smaller in the presence of a magnetic field at the same CIP volume percentage and increased as the CIP volume percentages grew, because the agglomeration in the samples became more. And also with a magnetic field, at the same CIP volume percentages, the strength of the MRE increased that led to the fatigue life of MRE increasing.